PENYULUHAN BERBASIS MULTIMEDIA DALAM MENCEGAH PERILAKU SEKS PADA REMAJA DI SMU NEGERI 11 PEKANBARU: multimedia-based, sexual behavior - Erianti, Susi; Adila, Dian Roza (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Adolescence is a change from childhood to adulthood, this is called puberty. Behavior negative aspect can be reduced by coaching oneself. Sexual behavior is all behavior that is related to normal and abnormal sexual activity. If this sexual behavior is carried out repeatedly to achieve sexual satisfaction and harming oneself and others, it is referred to as a sexual disorder. The purpose of this project community service is to increase students’ knowledge and understanding in preventing sexual behavior in adolescents. This project uses a questionnaire by conducting pre-test and post-test on 60 students of SMUN 11 Pekanbaru which were then analyzed using percentages. Evaluation of the achievement of community service objectives was carried out in a quantitative descriptive manner whether there was an increase in the percentage of the value of the pre test and post test. The result showed that an increasing of knowledge level from 65% into 87%. This suggestion to the school is make a schedule to do education using multimedia based - counseling that can make students easier to understand about the education topic. Keywords: Multimedia, Sexual Behavior, Youth